Practical ship hydrodynamics - Bertram, Volker (Butterworth-Heinemann, an imprint of Elsevier, 2012)
Provides an overview of hydrodynamic experimental and numerical methods for ship resistance and propulsion, maneuvering, seakeeping and vibration. Beginning with an overview of problems and approaches, this title introduces the marine applications of computational fluid dynamics and boundary element method